The (in)visibility of gender knowledge in the Physical Activity and Sport Science degree in Spain. Issue 4 (4th May 2018) - Serra, Pedrona; Soler, Susanna; Prat, Maria; Vizcarra, María Teresa; Garay, Beatriz; Flintoff, Anne
ABSTRACT: This paper draws on research that aimed to explore the construction of gender relations in sport and physical education (PE) through a national study of Spanish university degree curricula. Spain is a useful case study through which to explore gender knowledge within sport and PE degrees, because, unlike many other countries, it has a common, national curriculum framework for its Physical Activity and Sport Science (PASS) degrees. In addition, it has recently passed a new law concerning the introduction of gender knowledge in higher education (HE). Drawing on Bernstein's (1990) framework of the pedagogic device, this paper examines how this HE gender policy becomes recontextualised as universities and lecturers interpret and translate this into the pedagogical texts that make up the PASS curricula. Purposive sampling was used to select 16 of the 37 universities offering PASS degrees in 2012/2013. The research analysed 16 PASS documents at the degree level and 763 individual subject handbooks. Using discourse analysis, the results showed where and how gender knowledge was incorporated and the extent to which the topic was presented coherently throughout the documents. The analysis revealed five categories of the (in)visibility of gender knowledge within the universities' instructional discourse. Gender knowledge is largely ignored in PASS curricular documentation, appearing, at best, in highly superficial ways. Despite a national policy requirement on universities to incorporate gender knowledge, this study shows how recontextualisation processes within specific universities' pedagogic devices operate to marginalise such perspectives within PASS curricula. The research also revealed the significance of individual agents committed to gender equity being situated, and having influence, throughout the pedagogic device. The paper concludes that without a much wider, critical engagement in knowledge about gender equity, PASS degrees will continue to reproduce rather than disrupt the gender relations that have traditionally characterised the field.